MOTIVASI WISATAWAN MEMILIH SPA TRADISIONAL BALI - Sri Puspaadi, Ida Ayu (Pusat penelitian & Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2011)
The main aim of this study is to understand motivations of international tourists who choose traditional Balinese spa treatments and products. The study was conducted in international hotels at Nusa Dua Tourism Complex. An interview and a set of questionnaires were administered to 34 tourists used as the sample in this research. Non-probability and accidental sampling techniques were used in determining the 30 tourists who participated in this study. The collected data about tourists motivations were analyzed descriptively. The results of the study shows that the main push factors that motivate tourists to take Balinese traditional Spa treatments and products are to experience relaxation and health. Prestige is not their main motivation. The main pull motivation for tourists to have Balinese traditional spa treatments and products are: that the Balinese traditional spa treatments and products are available in the hotels where they stay and the high quality of Balinese traditional spa treatments and products.